Real-world treatment patterns among patients with non-muscle invasive bladder cancer (NMIBC) treated with intravesical Bacillus Calmette-Guerin (BCG). Issue 28 (1st October 2022) - Kumar, Neela; Balaji, Hiremagalur parthasarathy; Emond, Bruno; Manceur, Ameur M; Ghelerter, Isabelle; Pilon, Dominic; Lefebvre, Patrick; Imran, Nida Shafaat; Ellis, Lorie
Abstract : 404 Background: Intravesical BCG is a common treatment in high-risk NMIBC patients; however supply constraints and regimen demands for patients have been reported and may impact long term patient outcomes. This study examined treatment patterns in NMIBC patients receiving intravesical BCG. Methods: Adults with NMIBC treated with intravesical BCG during any line of therapy (LOT) on or after the index date (first date for transurethral resection of the bladder tumor [TURBT] or initiation of intravesical therapy) were selected from de-identified IBM MarketScan Commercial and Medicare Supplemental Databases (1/1/2010-2/28/2021) and Multi-State Medicaid Database (1/1/2010-12/31/2019). Classification of NMIBC on the index date required that patients have no prior systemic antineoplastic therapy, radiotherapy, or cystectomy. Treatment patterns were evaluated from the index date until the end of the NMIBC phase (earliest of initiation of systemic antineoplastic therapy, cystectomy, radiotherapy, diagnosis for metastatic cancer, end of insurance eligibility, or end of data availability). Discontinuation of a LOT was defined as having a treatment gap > 180 days for BCG (90 days for other agents) or switching to a new LOT. During each LOT, adequate BCG treatment was defined as having ≥5 claims during induction (first 42 days of treatment) and ≥2 claims during maintenance (beyond the first 42 days). Results: There were 5, 410 NMIBC patients treated with BCG over a mean (median) follow up of 25.5 (18.9) months. The population was 79% male; mean age was 67 years. The majority of patients only received a single LOT (76%; TABLE). The predominant first LOT was BCG (93.1% of NMIBC patients); however, the majority (69.8%) did not receive adequate BCG induction/maintenance in first LOT. Nearly half (46.4%) of first LOT patients had reassessment for disease progression by TURBT. BCG retreatment after a six-month lapse was observed as the predominant second LOT, with > 90% receiving inadequate BCG induction/maintenance. Conclusions: While intravesical BCG remains the most common therapy for NMIBC, less than a third of patients receive adequate BCG treatment in the first LOT; with this percentage further decreasing in the few patients who receive a subsequent LOT. In light of supply and demand constraints, results of this study further emphasize a need for additional treatment options that are effective, safe, and tolerable for patients with NMIBC.Treatments used, n (%) 1L N = 5, 410 2L N = 5, 410 3L+ N = 5, 410 Patients with LOT 5, 410 (100.0) 1, 277 (23.6) 380 (7.0) BCG 5, 341 (93.1) 1, 109 (86.8) 341 (89.7) Adequate BCG treatment 1, 611 (30.2) 77 (6.9) 12 (3.5) Mitomycin 104 (1.9) 132 (10.3) 30 (7.9) Gemcitabine 6 (0.1) 23 (1.8) 17 (4.5) Valrubicin 3 (0.1) 38 (3.0) 8 (2.1) Docetaxel 0 (0.0) 2 (0.2) 2 (0.5) Epirubicin 1 (0.0) 0 (0.0) 0 (0.0) No treatment 0 (0.0) 4, 133 (76.4) 5, 030 (93.0)